The Effect of GIR on Motivation, Vocabulary Mastery, and Reading Comprehension Ability - Rochana Purba Nurfauzi; Joko Priyana (Universitas Negeri Yogyakarta, 2020)
This research aims to: (1) describe the effect of GIR as a part of extensive reading; (2) compare the effectiveness between GIR and conventional learning; and (3) compare the effectiveness between GIR variation 1 and 2 on motivation, vocabulary knowledge and reading comprehension ability. The data were analyzed using: (1) the one sample t-test to investigate the effect of GIR; (2) the Helmert Contrast to investigate the difference in the effectiveness of GIR as well as the conventional technique; (3) the post-hoc test involving the Tukey to analyze which was more effective between GIR and conventional technique in students’ motivation, vocabulary knowledge and reading comprehension ability. The results of the study show that: (1) GIR has a significant effect on all dependent variables; (2) GIR is more effective than the control group in improving all dependent variables, except GIR variation 1 in reading comprehension ability has equal effect with conventional technique; (3) there is no difference in the effectiveness of GIR variation 1 and 2 in terms of improving students’ motivation, vocabulary knowledge, and reading comprehension skills. Key words: GIR, extensive reading, motivation, vocabulary knowledge, reading comprehension ability